Pemberdayaan Masyarakat melalui Inisiatif Pengadaan “Keranjang Sedekah Sampah” dan “Budidaya Maggot” untuk Pelestarian Lingkungan - Widyasari, Sindy; Muallidin, Isnaini; Fitriyani, Rifka Sukma; Yuniarto , Adam Anderson; Prayogo, Muchamad Imron; Putri, Della Nadia; Laresatu, Al Gibran Bintang; Pawitra, Hafizh Sina; Puspandari, Aulia Denova Candra Putri; Hakiim, Naufal; Karunia, Diyah (PUAN INDONESIA, 2025)
This community empowerment activity aims to increase awareness and involvement of youth and mothers in systematic waste management, as well as to realize a structured waste management strategy through the "Keranjang Sedekah Sampah" and "Maggot Cultivation" initiatives. This activity is carried out by providing socialization to provide basic knowledge about waste management, workshops to train practical skills such as waste sorting and maggot cultivation, mentoring to ensure effective program implementation, and evaluation to assess the success and sustainability of the program in the community. The results of this community service activity show the enthusiasm of participation, especially from mothers, in sorting waste and adopting maggot cultivation as a solution to organic waste management. This community service activity also succeeded in establishing "Keranjang Sedekah Sampah" points and a pilot site for "Maggot Cultivation". However, youth participation still needs to be improved, and there are challenges in the form of resistance to maggot cultivation. This program significantly improved the community's understanding of sustainable waste management, but further efforts are needed to increase youth involvement and optimize the program's sustainability